The Little Data Book 2001 - World Bank (The World Bank, 2001)
The Little Data Book 2001 provides a pocket-sized ready reference on key development data by country. The book presents 54 indicators for 207 countries and regional and income country groups.The Little Data Book is intended as a pocket reference tool for readers of World Development Indicators 2001 as well as for instructors, researchers, and students who work with development data. The Little Data Book 2001 can be purchased separately or as a set with the World Bank Atlas 2001